Analysis of Islamic Business Feasibility Study on New Product Development (Case Study of Oatmeal Soap Is An Natural, Eco Friendly Body Cleanser) - Desi, Agil Cintia; Ridlwan, Ahmad Ajib (Imara: Jurnal Riset Ekonomi Islam, 2024)
Background. The most common skin problems in Indonesia include acne, dry skin, dull skin, scabies, and serious diseases such as leprosy. Based on research (Pratiwi, 2024), around 60% of women in Indonesia complain of dull skin, large pores, and acne. Despite this, Indonesia has made progress in dealing with serious skin diseases such as leprosy. The new development product Eco-Friendly Oatmeal Body Cleanser Soap can provide solutions to overcome skin diseases, as well as natural and environmentally friendly product ingredients and packaging.Purpose. This article discusses the importance of integrating business feasibility analysis, Islamic economic principles, and environmental sustainability in the development of oatmeal soap. The research shows that this product meets halal standards and provides skin health benefits while supporting environmental sustainability. The results are expected to serve as a reference for business practitioners to create products that are economically profitable and beneficial to society.Method. The qualitative research methodology in this article employs in-depth interviews with Islamic economic experts, consumers, and natural ingredient industry players. The aim is to explore the views and experiences of informants regarding the feasibility of oatmeal soap from sharia and sustainability perspectives. The data is analyzed thematically to identify relevant patterns.Results. The research findings indicate that oatmeal soap has significant potential as a natural, halal, and eco-friendly product. Consumers are interested in products free from harmful chemicals, and Islamic economic experts affirm that this product meets the business feasibility criteria within the sharia context.Conclusion. The development of oatmeal soap as a natural and eco-friendly product demonstrates high business feasibility, supported by strong consumer interest and compliance with sharia principles